POSITIVE PSYCHOLOGY AND POSITIVE ORIENTATION - Vesna Petrović (Exercise and Quality of Life, 2010)
Positive psychology represents a 21st century movement in psychology. It is a psychology aimed at researching optimal human functioning that empirically studies, first and foremost, the concept of happiness, in addition to life satisfaction, optimism, virtues and suchlike notions, which are used to measure the growth and development of human potential and subjective well-being. This line of conceptualization and research is based on the disease model and opens up new perspectives for both psychology as a science as well as the people it is intended for. This paper elaborates the basic ideas and results of certain explorations relative to positive psychology and positive orientation which comprises optimism, self-esteem and life satisfaction.